A Predictive Model of Patient Transfer Waiting Time from the Emergency Installation (ER) to the Inpatient Room - Irwan Irwan; Fatmawati Fatmawati; Rusmanwadi Rusmanwadi; Ade Wahyu Alti; Maya Syafni (Indonesian Journal of Global Health Research, 2026)
The waiting time for patient transfer from the Emergency Department (ER) to the inpatient ward is an important indicator in hospital health services. This process reflects the efficiency and effectiveness of the service flow, and can affect patient satisfaction, safety, and overall service quality. Delays in patient transfer are often a problem that has the potential to increase the risk of medical complications, prolong the length of stay, and increase the workload of health workers. This study aims to determine the predictive factors for patient transfer time from the ER to the inpatient (a case study in the ER Room of Dr. M. Djamil Padang General Hospital. This study uses an observational analytical quantitative research design with a cross-sectional approach. The sampling technique in this study is proportional random sampling. The sample consisted of all 283 patients transferred from the Emergency Department (ER) to the ward at Dr. M. Djamil Padang General Hospital, with specified inclusion and exclusion criteria. Data were collected through interviews and observations. Bivariate data analysis used Smart PLS to determine predictive factors for patient transfer waiting time from the ER to the ward. The results showed that ER factors significantly influenced System Factors and Room Factors, but did not directly influence patient transfer time.